Narirutin downregulates lipoxygenase-5 expression and induces G0/G1 arrest in triple-negative breast carcinoma cells - Singh, Shilpi; Maurya, Akhilesh Kumar; Meena, Abha; Mishra, Nidhi; Luqman, Suaib (Biochimica et biophysica acta. General subjects, 2023)
Triple-negative breast cancer (TNBC) accounts for 20% of breast cancer that does not express HER2, progesterone and estrogen receptors. It is associated with a high mortality rate, morbidity, metastasis, recurrence, poor prognosis and resistance to chemotherapy. Lipoxygenase-5 (LOX-5), cyclooxygenase-2 (COX-2), cathepsin-D (CATD), ornithine decarboxylase (ODC) and dihydrofolate reductase (DHFR) are involved in breast cancer carcinogenesis; hence, there is a pressing need to identify novel chemicals that targets these enzymes. Narirutin, a flavanone glycoside abundantly present in citrus fruits, is reported to have immune-modulatory, anti-allergic and antioxidant potential. Still, the cancer chemopreventive mechanism against TNBC has not been explored. In vitro experiments, enzyme activity, expression analysis, molecular docking and MD simulation were carried out. Narirutin suppressed the growth of MDA-MB-231 and MCF-7 in a dose-proportional manner. The pronounced effect with >50% inhibition was observed in SRB and MTT assays for MDAMB-231 cells. Unexpectedly, narirutin suppressed the proliferation of normal cells (24.51%) at 100 μM. Further, narirutin inhibits the activity of LOX-5 in cell-free (18.18 ± 3.93 μM) and cell-based (48.13 ± 7.04 μM) test systems while moderately affecting COX-2, CATD, ODC and DHFR activity. Moreover, narirutin revealed a down-regulation of LOX-5 expression with a fold change of 1.23. Besides, MD simulation experiments confirm that narirutin binding forms a stable complex with LOX-5 and improves the stability and compactness of LOX-5. In addition, the prediction analysis demonstrates that narirutin could not cross the blood-brain barrier and did not act as an inhibitor of different CYPs. Narirutin could be a potent cancer chemopreventive lead for TNBC, further paving the way for synthesizing novel analogues. [Display omitted] •Narirutin suppressed the proliferation of triple-negative breast cancer cells.•It inhibits the activity of LOX-5 and down-regulates its expression.•Narirutin forms robust binding and stable molecular interaction with LOX-5.•It arrests G0/G1 phase and increases the sub-diploid population.•Narirutin did not cross BBB and a non-inhibitor of CYPs.